Rancang Bangun Sistem Informasi Pengadaan Barang Menggunakan Teknologi Cloud Computing - Deni Hardiansyah; Ade Priyatna (STMIK Budi Darma, 2023)
Cloud computing or what is commonly called cloud computing is being widely discussed in this digital era, the ease of procuring servers is very helpful in the system design process within an organization or company in implementing it, PT Arcelon uses this technology in building a procurement information system to speed up the development stage, procurement of goods and management of goods in and out of goods is currently still in a manual process so a goods procurement information system is needed in the form of a web that can be accessed from the internet network to be able to process and make reporting in every transaction in and out of goods, PT Arcelon has a problem in build a system into a server, by buying a very expensive server, long installation and procurement time, and maintenance that is done often causes a problem, such as an electric short circuit when carrying out maintenance, hindering ongoing business processes in carrying out system deployments that are being carried out because it requires a Cloud Computing technology to bridge this where the system development model that will be used is the waterfall SDLC model (waterfall) by utilizing cloud technology which can guarantee very high server availability. high and can serve many requests from many users under certain conditions. The results of the study show that the system built makes it easier for companies to carry out transactions both procurement, checking, and entering and leaving goods.